2007
DOI: 10.1016/j.brainres.2007.06.102
|View full text |Cite
|
Sign up to set email alerts
|

Widespread disruption in brain activation patterns to a working memory task during cocaine abstinence

Abstract: Cocaine abstinence is associated with impaired performance in cognitive functions including attention, vigilance and executive function. Here we test the hypothesis that cognitive dysfunction during cocaine abstinence reflects in part impairment of cortical and subcortical regions modulated by dopamine. We used functional magnetic resonance imaging (fMRI) to study brain activation to a verbal working memory task in cocaine abusers (n = 16) and healthy controls (n = 16). Compared to controls, cocaine abusers sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
88
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 46 publications
(57 reference statements)
15
88
0
4
Order By: Relevance
“…The mechanisms through which cocaine might adversely affect PM functions remain unclear. On the basis of the results from their fMRI study, Tomasi et al (2007) argue that a prior history of cocaine use disrupts the operation of those dopaminergic systems in the prefrontal cortex which underpin executive functioning. Given the key role of executive functions in supporting PM processes this might account for the adverse association between cocaine use and PM functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms through which cocaine might adversely affect PM functions remain unclear. On the basis of the results from their fMRI study, Tomasi et al (2007) argue that a prior history of cocaine use disrupts the operation of those dopaminergic systems in the prefrontal cortex which underpin executive functioning. Given the key role of executive functions in supporting PM processes this might account for the adverse association between cocaine use and PM functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this core I-RISA hypothesis, neuroimaging studies in drug addicted individuals demonstrate ACC and OFC hyperactivations during drug-related cue reactivity (2), including craving (3,4) and hypoactivations during performance of neutrally valenced cognitive tasks (5)(6)(7)(8)(9). Because these hypoactivations in addicted individuals could reflect impaired performance (5-8) or decreased engagement (9), in the current study we set out to determine whether ACC hypoactivations in addiction can still be observed in groups matched for overt performance on an emotionally salient task.…”
mentioning
confidence: 87%
“…We have shown that small alterations to mPFC dopamine connectivity lead to sizeable changes in the pyramidal neuron morphology and excitability and, consequently, to changes in cognitive processing and responses to drugs of abuse (Grant et al, 2007;Manitt et al, 2011Manitt et al, , 2013Pokinko et al, 2014). Similarly, dopamine function in the human prefrontal cortex has been shown to play a critical role in higherorder cognitive processing, including behavioral inhibition and salience attribution, as well as in the regulation of subcortical reward circuitry (Robbins et al, 1994;Rogers et al, 1999;Tomasi et al, 2007;Goldstein and Volkow, 2011). Thus, by disrupting prefrontal cortex dopamine maturation, drug use in adolescence likely induces deficits in these processes, increasing vulnerability to develop addiction.…”
Section: Dcc-mediated Effects Of Amphetamine On the Sculpting Of Mpfcmentioning
confidence: 99%
“…Thus, by disrupting prefrontal cortex dopamine maturation, drug use in adolescence likely induces deficits in these processes, increasing vulnerability to develop addiction. Indeed, compelling evidence shows prefrontal cortex dysfunction and associated cognitive deficits in stimulant drug abusers (Verdejo-García et al, 2006;Tomasi et al, 2007;Woicik et al, 2011;Ersche et al, 2011;Goldstein and Volkow, 2011;Kohno et al, 2014;). Furthermore, prefrontal cortex activation in adolescent subjects appears to predict levels of future substance use and dependence symptoms, particularly in individuals who are already high-frequency drug users (Mahmood et al, 2013).…”
Section: Dcc-mediated Effects Of Amphetamine On the Sculpting Of Mpfcmentioning
confidence: 99%